(untitled) (City Dental College Journal, 2018)
Aims: This cross-sectional study was conducted in rural areas of Bangladesh to assess and compare the state of oral health among the arsenic exposed population affected through drinking water with the non-exposed group. Materials and Methods: A total of 400 respondents were interviewed and examined through a structured questionnaire and a checklist. Exposed group was included with or without the signs of arsenicosis. Results: Among them, 200(50%) were found exposed to arsenic and the rest 200(50%) were in non-exposed group. Study showed that 6% respondents were suffering from sensitivity of teeth, and 24.5% and 20% developed pigmentation on gingival and tongue surfaces, respectively, who used to take arsenic contaminated water, in comparison to non-exposed group, 10.9%, 5%, 0.5%, respectively. Arsenic exposed group had tooth abrasion 24%, while it was 4.5% in non-exposed group. Less caries (18.5%) was found among the arsenic exposed group than the non-exposed group (25.9%). Conclusion: Arsenic might have influence on enamel hypoplasia and this low tendency of occurring carries. DOI: http://dx.doi.org/10.3329/cdcj.v10i1.13834 City Dent. Coll. J Volume-10, Number-1, January-2013